Improving Fiscal Federal Relations for a Stronger Mexico - Caldera Sánchez, Aida (OECD Economics Department Working Papers, 2013)
Mexico has achieved a high degree of decentralisation in public services, but the Mexican fiscal federal system has important shortcomings. States and municipalities have become heavily dependent on federal transfers to finance a growing share of public spending. This leaves the burden of raising tax revenues falling almost exclusively on the federal government and reduces incentives for efficient spending and active tax collection at the subnational level. It can also lead to moral hazard and fiscal slippages. The federal government should harden the budget constraint on sub-national governments by limiting further increases in transfers and avoiding extraordinary transfers. Promoting the implementation of stronger fiscal rules, such as rules on deficits and debt ceilings, could also help to harden budget constraints and to ensure greater fiscal discipline. States should be given more taxing powers, if they are to collect a larger share of total revenues. Greater accountability and clarification of spending responsibilities could also contribute to improve the efficiency of spending among states and municipalities